(3QaY GdEUQ Yf bVGI eUQs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s ((3JdejP GdeUfa GdMGaX GdSNGhi s)
(3ChdgG (B:s
(3GdMeO ddg abO hbaJ Ydi QLR ai PcQ ef hdi GdbVGA HGdOjGQ GdeUQjI s
(3BNQgG (B:s
(3BNQ GdehLhO efg HYO GdQLhY ef hbYI Yjf LGdhJ hSdWfI GdXGgQ HjHQS hPdc ai SfI JSY hNeSjf abHV Ydjg Ke CaQL Yfg hGSJbQ YhVg s
(3HgG fXGe GdJYbjHIs
(3cJHJ HNW eged GdfbW CMjGfkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJGQjNs